Active Model Patterns with Interactive Model Transformation - Mészáros, Tamás; Levendovszky, Tihamér; Mezei, Gergely (Electronic Communications of the EASST, 2011)
With the proliferation of domain-specific languages, the generalization of OO patterns is a natural demand. Concepts and tools supporting pattern specification and execution for arbitrary domain-specific languages facilitate to meet these requirements. Our previous work introduced the Active Model Pattern Infrastructure and possible realizations for its static aspect. In this paper, we contribute a realization for the operational aspect of the framework. We propose graph rewriting-based interactive model transformation to describe and automate often recurring operational patterns in domain-specific modeling. We have extended a general transformation system with localized application of the rules and facilitate run-time customization possibilities for the domain engineer to influence the execution of the operations. We can specialize this approach to provide an implementation of the static aspect as well. We have realized our solution in the Visual Modeling and Transformation System.